IgE and IgG4 epitopes revealed on the major fish allergen Lat c 1. (March 2021) - Sharp, Michael F.; Taki, Aya C.; Ruethers, Thimo; Stephen, Juan N.; Daly, Norelle L.; Lopata, Andreas L.; Kamath, Sandip D.
Highlights: The IgE- and IgG4 -binding to major fish allergen Lat c 1.01 was investigated. The IgG4 binding was patient-specific regardless of the age group. Two specific IgE epitopes were identified at the C- and N-terminal regions. Highlighted the importance of epitope analysis for fish allergy management. Abstract: Background: The IgE- and IgG4 -binding patterns of the major fish allergen parvalbumins are not clearly understood. IgE antibody-binding to parvalbumin from Asian seabass, Lat c 1.01, is implicated in up to 90 % of allergic reactions, although the region of IgE or IgG4 epitopes are unknown. In the present study, we characterized the specific IgE- and IgG4 -binding regions of Lat c 1.01 using serum from pediatric and adult patients with clinically-confirmed fish allergy. Methods: A comparative investigation of patient IgE- and IgG4 -binding to recombinant Lat c 1.01 was performed by immunoblotting and indirect ELISA using serum from 15 children and eight adults with clinically confirmed IgE-mediated reactions to fish. The IgE- and IgG4 -binding regions of Lat c 1.01 were determined by inhibition ELISA using seven overlapping peptides spanning the entire 102 amino acid sequence. Elucidated IgE-binding regions were modelled and compared to known antibody-binding regions of parvalbumins from five other fish species. Results: Ninety five percent (22/23) patients demonstrated IgE-binding to rLat c 1.01, while fewer patients (10/15 children and 7/8 adults) demonstrated robust IgG4 binding when determined by immunoblots. IgE-binding for both cohorts was significantly higher compared to IgG4 -binding by ELISA. All patients in this study presented individual IgE and IgG4 epitope-recognition profiles. In addition to these patient-specific antibody binding sites, general IgE epitopes were also identified at the C- and N-terminal regions of this major fish allergen. Conclusions and Clinical relevance: Our findings demonstrate two specific IgE epitopes on parvalbumin from Asian seabass, while IgG4 binding is much lower and patient specific. This study highlights the importance of advancement in epitope analysis regardless of the age group for diagnostics and immunotherapies for fish allergy.